Periscoping the 2019 Nigerian Xenophobic Experience in South Africa - Nnani, Nnaemeka Emannuel; Muoneke, Chukwuemeka Vincent (Social Science Research, 2023)
The xenophobic attacks on foreign nationals residing in South Africa are no novel to Nigerian(s) and the entire African countries. The government of South Africa historically have not done anything tangible to tackle this problem that threatens her mutual cooperation with the African countries particularly Nigeria. This paper among other issues intends to assess xenophobic attacks against Nigerians in South Africa and its reoccurring impact on contemporary Nigeria-South African relations. Secondary method of data collection and content analysis approach were employed while using realist conflict theory to aid in the understanding of the phenomenon understudy. Our key findings revealed that xenophobic attacks against Nigerians in South Africa are well recorded, yet the South African government have not done anything tangible to stop its reoccurrence. We suggested the urgent need for governments of both countries to ensure that adequate policies and mechanisms are put in place to permanently hurt the ugly incidence and avoid it reoccurrence and ensure that this policies and mechanisms are enacted into their laws making xenophobia a crime punishable by the law.